Wyspa dnia poprzedniego - Eco, Umberto (Warszawa : Panstwowy Instytut Wydawniczy, 1995)
A novel about a shipwreck in the South Pacific Ocean.
Translation of: L'isola del giorno prima.
Keywords: Shipwrecks -- South Pacific Ocean -- Fiction